2020
DOI: 10.1007/s40843-020-1464-6
|View full text |Cite
|
Sign up to set email alerts
|

Mass production of high-performance single atomic FeNC electrocatalysts via sequenced ultrasonic atomization and pyrolysis process

Abstract: Mass production of highly efficient, durable, and inexpensive single atomic catalysts is currently the major challenge associated with the oxygen reduction reaction (ORR) for fuel cells. In this study, we develop a general strategy that uses a simple ultrasonic atomization coupling with pyrolysis and calcination process to synthesize single atomic FeNC catalysts (FeNC SACs) at large scale. The microstructure characterizations confirm that the active centers root in the single atomic Fe sites chelating to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…High-temperature operation with mature technology is the most commonly used method to synthesize all kinds of DACs [166][167][168][169]. Simply speaking, the metal precursor of the target product is mixed with the carbonaceous material as the supporting substrate and then pyrolyzed [170,171]. However, due to the instability under high temperature, a series of different catalytic site configurations outside the ideal dual-atom structure will be generated, such as the single metal sites, irregular metal sites of mononuclear DACs and even small part of agglomeration.…”
Section: High-temperature Pyrolysis Methodsmentioning
confidence: 99%
“…High-temperature operation with mature technology is the most commonly used method to synthesize all kinds of DACs [166][167][168][169]. Simply speaking, the metal precursor of the target product is mixed with the carbonaceous material as the supporting substrate and then pyrolyzed [170,171]. However, due to the instability under high temperature, a series of different catalytic site configurations outside the ideal dual-atom structure will be generated, such as the single metal sites, irregular metal sites of mononuclear DACs and even small part of agglomeration.…”
Section: High-temperature Pyrolysis Methodsmentioning
confidence: 99%
“…Moreover, the isolated Fe sites could be loaded on a golf-ball-like/cube-like porous carbon substrate or porous carbon nanospheres, part of which could also realize gram-level production and good ZAB performance. [136][137][138] Besides, research found that a suitable surface wettability of electrocatalysts has a positive impact on forming a three-phase boundary during the catalytic process, facilitating water removal, and abundant oxygen diffusion. [139] Therefore, a highly effective Fe-based SAC for ORR and ZABs was reported via fabricating a mesoporous structure and tuning the hydrophobicity/hydrophilicity properties (Figure 6d).…”
Section: Nanostructuresmentioning
confidence: 99%
“…1a). The aqueous solution of tetraamminepalladium nitrate ([Pd(NH 3 ) 4 ](NO 3 ) 2 , 2.45 mmol L −1 ) was atomized into very small drops of ~40 μm 3 in volume by an ultrasonic atomizer 27,28 and sprayed at a rate of ~40 mL h −1 onto FeO x , which was spread out evenly on the iron basin. The infrared lamps and the heating plate were employed to remove the moisture quickly by heating the FeO x powders to over 60 °C.…”
Section: Synthesis Of Pd Sacs With the Precursor-atomization Strategymentioning
confidence: 99%